PRAKTIK KEHIDUPAN EKONOMI PEKERJA WANITA PADA PABRIK ROKOK GUDANG GARAM MERAH (APACHE) DALAM TEORI GENDER - Wahibatul Maghfuroh (JAS : Jurnal Ahwal Syakhshiyyah, 2019)
Women work because of the heavy family burden, and the lower economic demands cause a female worker to work at the Gudang Garam Merah company known as the "Apache Cigarette" in Paiton Probolinggo so that it can ease the burden on the husband and the burden on their family. . With the wages or income they have received, it can ease their family's burden and can create a prosperous family. And this can be seen in women workers who work at the Red Salt Warehouse Cigarette company. The formulation of the problem is how the reality that occurs in women who work in the Red Salt Warehouse (Apache) in Paiton Probolinggo and how the economic life practices of women workers in the red salt cellar cigarette factory in Paiton Probolinggo and analyzed with Gender theory. Data analysis method used is qualitative data analysis with descriptive analytic or content analysis (Content Analysis). author's analysis of women working at Gudang Garam cigarettes Behind the high level of cigarette consumption in Indonesia, there is an industry worth tens of millions with hundreds of thousands of people who depend their lives on this industry. The types of labor that are absorbed by the tobacco industry are mostly female and this is a custom that occurs in the Paiton area. to balance the role in the husband's family must have a permanent job that generates money to work with one another, to meet each other's daily needs so that there is no imbalance between the husband and wife in working in the household.